Rapid Adoption of Telemedicine in Rheumatology Care During the COVID‐19 Pandemic Highlights Training and Supervision Concerns Among Rheumatology Trainees - Su‐Ann Yeoh; Kristen Young; Michael Putman; Sebastian Sattui; Richard Conway; Elizabeth Graef; Adam Kilian; Maximilian Konig; Jeffrey Sparks; Manuel Ugarte‐Gil; Laura Upton; Francis Berenbaum; et al. (ACR Open Rheumatology, 2022)
Objective To evaluate the impact of telemedicine use during the coronavirus disease 2019 (COVID‐19) pandemic on rheumatology trainees. Methods A voluntary, anonymous, web‐based survey was administered in English, Spanish, or French from August 19 to October 5, 2020. Adult and pediatric rheumatology trainees were invited to participate via social media and email. Using multiple‐choice questions and Likert scales, the survey assessed prior and current telemedicine use, impact on training, and supervision after COVID‐19 prompted rapid telemedicine implementation. Results Surveys were received from 302 trainees from 33 countries, with 83% in adult rheumatology training programs. Reported telemedicine use increased from 13% before the pandemic to 82% during the pandemic. United States trainees predominantly used video visits, whereas outside the United States telemedicine was predominantly audio only. Most (65%) evaluated new patients using telemedicine. More respondents were comfortable using telemedicine for follow‐up patients (69%) than for new patients (25%). Only 39% of respondents reported receiving telemedicine‐focused training, including instruction on software, clinical skills, and billing, whereas more than half of United States trainees (59%) had training. Postconsultation verbal discussion was the most frequent form of supervision; 24% reported no supervision. Trainees found that telemedicine negatively impacted supervision (50%) and the quality of clinical teaching received (70%), with only 9% reporting a positive impact. Conclusions Despite widespread uptake of telemedicine, a low proportion of trainees received telemedicine training, and many lacked comfort in evaluating patients, particularly new patients. Inadequate supervision and clinical teaching were areas of concern. If telemedicine remains in widespread use, ensuring appropriate trainee supervision and teaching should be prioritized.